The Healthy Eating Plate and periodontal health knowledge in undergraduate students of Faculty of Dentistry Universitas Padjadjaran - Rusjanti, Janti; Solihati, Salma Kamila; Zubaedah, Cucu (Padjadjaran Journal of Dentistry, 2018)
Introduction: Periodontal disease is a multifactorial disease that attacks periodontal tissue caused by bacterial plaque and calculus, and also nutritional deficiency. Applying a healthy dietary habit will be able to prevent the occurrence of periodontal disease. The purpose of this study was to discovered description of the Healthy Eating Plate habit and periodontal health knowledge in undergraduate students of Faculty of Dentistry Universitas Padjadjaran. Method: This research was quantitative with two questionnaire instruments; the first contained the food variety and the proportion consumed by respondents, and the second contained questions regarding the periodontal health. The samples were as much as 137 undergraduate students of Faculty of Dentistry Universitas Padjadjaran batch 2015, taken with an accidental random sampling technique. Results: The nutritional proportion of all respondents were as follows: at breakfast, 27.5% of carbohydrate, 25.1% of protein, 24.3% of vegetables, and 23.4% of fruits; at lunch, 29.1% of protein, 27.1% of carbohydrates, 19.8% of vegetables, and 24.4% of fruits; at dinner, 27% of protein, 23% of carbohydrate, 20.9% of vegetables, and 20.1% of fruits. The level of periodontal knowledge was 68.94%. Conclusion: The respondent's dietary habit was close enough to the indicators of the Healthy Eating Plate, with a moderate level of periodontal health knowledge.